2001
DOI: 10.1046/j.1524-4741.2001.99124.x
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Duct Carcinoma of the Breast: Clinical and Histopathologic Factors and Association with Recurrent Carcinoma

Abstract: There has been a recent increase in the diagnosis of in situ duct carcinoma of the breast (DCIS) as a result of mammographic screening. DCIS is heterogeneous in appearance and likely in prognosis. There is no generally accepted model to predict progression to invasive carcinoma. We investigated the prognostic effect of clinical presentation and pathologic factors for women diagnosed with primary DCIS. A cohort of 124 patients was accrued between 1979 and 1994 and was followed to 1997; 78 had DCIS detected mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 35 publications
0
56
0
Order By: Relevance
“…21 The recent increase in the diagnosis of DCIS is a result of current routine mammographic screening. 11 Of critical importance to the diagnosis of intraductal carcinoma is the integrity of the basement RIBEIRO-SILVA et a1 membrane. When carcinoma is confined to the duct system, without violation of the basement membrane, axillary lymph node involvement is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…21 The recent increase in the diagnosis of DCIS is a result of current routine mammographic screening. 11 Of critical importance to the diagnosis of intraductal carcinoma is the integrity of the basement RIBEIRO-SILVA et a1 membrane. When carcinoma is confined to the duct system, without violation of the basement membrane, axillary lymph node involvement is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…The subgroup data of three RCTs were analyzed because tumor characteristics of interest were not included in their multivariate analysis [16,18,21]. Seven observational studies that did not report the risk estimate or its corresponding 95% confidence interval were not included in the pooled analyses [52][53][54][55][56][57][58].…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Compared to those without postoperative mammogram, Vargas et al found that women with postoperative mammogram have lower IBTR (HR = 0.21 with P-value = 0.04) [58]. Method of detection Three RCTs and nine observational studies examined the association between method of detection and outcome [15,17,21,26,28,30,34,35,[44][45][46]56]. We excluded one observational study because its relative risk estimate was not reported [56].…”
Section: Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, tumor grading has been associated with recurrence, progression, and invasion carcinoma (e.g., breast DCIS), but such an association is highly dependent on tumor heterogeneity and mixed grading (e.g., presence of more than one grade), which offers significant challenges to the pathologists as mixed grading appears to be present in 50 percent of patients [8]. A recent study indicates that detailed segmentation and multivariate representation of nuclear features from H&E stained sections can predict DCIS recurrence [9] in patients with more than one nuclear grade.…”
Section: Review Of Previous Researchmentioning
confidence: 99%